2005
DOI: 10.1080/00016480510038554
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of electrodes of a cochlear implant into the vestibular system: Intra- and postoperative electrophysiological analyses

Abstract: A cochlear implant device is normally inserted into the scala tympani via a posterior tympanotomy and cochleostomy. There has been no previous report of displacement of the array into the vestibular part of the labyrinth. The authors present and discuss the audiological and electrophysiological measurements of a case in which part of the array herniated through into the vestibule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…In that case, the electrode array was misinserted into the lateral semicircular canal, passing the vestibule; however, intraoperative measurements showed impedance and ECAP responses, suggesting a reasonable function of the inner ear and of the implant [8]. Pau et al reported a case of displacement of electrodes into the vestibule in a 68-year-old man with progressive hearing loss and a normal inner ear [9]. An uneventful right cochlear implant surgery was performed.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In that case, the electrode array was misinserted into the lateral semicircular canal, passing the vestibule; however, intraoperative measurements showed impedance and ECAP responses, suggesting a reasonable function of the inner ear and of the implant [8]. Pau et al reported a case of displacement of electrodes into the vestibule in a 68-year-old man with progressive hearing loss and a normal inner ear [9]. An uneventful right cochlear implant surgery was performed.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, accidental insertion of an electrode array into the vestibule of a morphologically normal inner ear results in anacusis and vestibular symptoms such as vertigo or disequilibrium [7][8][9]. Tange et al reported a case of electrode misinsertion into the vestibular system in a 55-year-old man without IEM.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, whether the ECAP recording technology developed for cochlear implants can be applied to vestibular implantation has not been systematically studied. In a previous case report of a human patient [36] vestibular ECAPs were recorded when the electrodes of a cochlear implant were accidentally misdirected into the vestibular part of the labyrinth. If ECAPs could be reliably evoked from a vestibular implant, the method would have two potential advantages relative to measuring EEMs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by Lassig et al (5) showed that the reason for revision was an electrode array positioning problem in 13% of 58 patients undergoing revision surgery. Others have published case reports describing electrode arrays that deviate toward the vestibulum (6,7). Both foldover of the electrode array and the depth of insertion are also major factors for eventual speech perception (1,2,4,8).…”
mentioning
confidence: 99%